Inovasi Kepemimpinan Kepala Madrasah terhadap Motivasi dan Kinerja Guru dalam Mengembangkan Pembelajaran di MAN 2 Langkat - Aisyah Nurcahyani; Khikmatu Zahwa; Elsya Aminatun Husna; Herlangga Pratama; Sartika Hutasuhut; Muammar Abian Arby Ramadhan (Asosiasi Riset Ilmu Pendidikan Indonesia, 2025)
This study aims to describe the innovative leadership practices of madrasah principals and their impact on teacher motivation and performance in developing learning at MAN 2 Langkat. The research approach used a descriptive qualitative method with data collection techniques through observation, interviews, and documentation of madrasah principals, teachers, and school staff. The results show that madrasah principals at MAN 2 Langkat implement innovative leadership by creating a comfortable work environment, providing full support to teachers in developing learning, and serving as positive role models. This support includes providing opportunities for teachers to develop creativity, encouraging the use of digital learning media, and implementing project-based learning. In addition, madrasah principals involve teachers in the school activity planning process, facilitate collaboration between teachers, and build partnerships with external parties to support educational programs. Teachers responded positively to this leadership style by demonstrating increased work enthusiasm, a sense of appreciation, and the courage to try new teaching methods. These changes have resulted in increased variety and quality of classroom learning processes. Students also experience a more engaging and interactive learning experience, motivating them to actively participate. These findings demonstrate that caring, communicative, and open leadership can create a work environment that supports teacher professional growth while improving the quality of learning. Madrasah principals' leadership innovations have been proven to significantly contribute to school progress, both in terms of teacher motivation and performance, as well as student learning outcomes.